2020
DOI: 10.1037/pro0000262
|View full text |Cite
|
Sign up to set email alerts
|

Development and randomized-controlled evaluation of a web-based training in evidence-based trauma therapy.

Abstract: Although trauma-focused interventions are effective in treating patients with PTSD, they are not frequently used in clinical practice. To address this gap, the present study aimed to develop and evaluate a web-based training for trauma-focused therapy. Our main objective was to increase the knowledge and competencies of current and future licensed psychotherapists in the core procedures that have been identified as efficacious treatment components. The web-based training consists of modules on diagnostics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Statistical analyses were performed using the Statistical Package for the Social Sciences SPSS 23.0 and JMP version 13.2.0. For the purpose of data reduction, all 30 items regarding the subjective state of knowledge and competencies, subjective emotional competencies, and self-efficacy expectations were subjected to a principal component analysis (PCA;Sansen et al, 2019). The PCA resulted in six factors, including self-efficacy expectation, general knowledge (Cronbach's alpha: .92), specific competences (Cronbach's alpha: .75), self-care (Cronbach's alpha: .77), self-reflection (Cronbach's alpha: .71), and overcoming concerns (Cronbach's alpha: .55).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Statistical analyses were performed using the Statistical Package for the Social Sciences SPSS 23.0 and JMP version 13.2.0. For the purpose of data reduction, all 30 items regarding the subjective state of knowledge and competencies, subjective emotional competencies, and self-efficacy expectations were subjected to a principal component analysis (PCA;Sansen et al, 2019). The PCA resulted in six factors, including self-efficacy expectation, general knowledge (Cronbach's alpha: .92), specific competences (Cronbach's alpha: .75), self-care (Cronbach's alpha: .77), self-reflection (Cronbach's alpha: .71), and overcoming concerns (Cronbach's alpha: .55).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the relationship of sociodemographic factors, knowledge, and competences with willingness to carry out trauma-focused therapy, as well as their predictive value in terms of willingness in a regression analysis. The evaluation of the web-based training showed that it addresses both knowledge as well as competencies relevant to trauma diagnostics and treatment, emotional competencies, and selfefficacy expectations, and actually leads to an increase in all these areas (Sansen et al, 2019). Most of the training's outcome variables (general knowledge, specific competences, self-care, overcoming concerns, selfefficacy expectations, knowledge test) were associated with willingness to carry out trauma-focused therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations